'Do you think it's a crime?' Building joint understanding of victimisation in calls for help. (November 2019) - Tennent, Emma
Society has a moral obligation to help victims, but who is recognised as a victim is a contentious issue. Social interaction is a key site where shared understandings of victimisation are built. This article analyses calls to a Victim Support helpline using conversation analysis and membership categorisation analysis. Callers described experiences of crimes to account for requesting help. Call-takers claimed the rights to describe and assess callers' experiences in terms of institutional constraints. Call-takers disavowed the category crime to deny callers' requests and ascribed the category crime to accountably offer help. Participants negotiated their respective rights to describe callers' experiences and determine the kind of help needed. The analyses demonstrate how participants' different understandings of victimisation were consequential for the delivery or withholding of support.